2018
DOI: 10.1002/lary.27291
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of microscopic thyroglossal duct tissue superior to the hyoid bone

Abstract: 2b. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The thyroglossal duct is the portion of the tract that remains connected to the base of the tongue after thyroid gland descent and is thought to involute at 7–10 weeks gestation. Persistence of portions of the thyroglossal duct can lead to formation of thyroglossal duct cysts (TGDCs), remnants, or tracts [1, 2]. The prevalence of TGDCs is thought to be roughly 7% of the population, with 1% of those developing into TGDC carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroglossal duct is the portion of the tract that remains connected to the base of the tongue after thyroid gland descent and is thought to involute at 7–10 weeks gestation. Persistence of portions of the thyroglossal duct can lead to formation of thyroglossal duct cysts (TGDCs), remnants, or tracts [1, 2]. The prevalence of TGDCs is thought to be roughly 7% of the population, with 1% of those developing into TGDC carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…This raises anxiety for the patient, parent, and surgeon, in addition to a resultant increase in healthcare costs. The suprahyoid area is particularly relevant to the TGDC surgeon because there often exists single or multiple microscopic ducts and/or aborization of the tract, none of which can be visualized or palpated by the surgeon and therefore may not be excised during a primary procedure 5,7,8–10 . In this study, a large majority, 79% (37 of 47) of patients, had evidence of microscopic TDGC disease in the area superior to the hyoid.…”
Section: Discussionmentioning
confidence: 78%
“…Unlike the perihyoid area, where the hyoid bone serves as an easily identifiable surgical landmark, there are no obvious surgical landmarks in the suprahyoid area. Garcia et al have shown that microscopic disease was present superior to the hyoid bone in 74% of all cases and in 100% of revision cases 7 . These data underscore the importance of complete removal of TGDC superior to the hyoid in order to avoid persistent or recurrent disease and a revision procedure.…”
Section: Introductionmentioning
confidence: 90%
“…Despite these advances in our understanding of the anatomy of thyroglossal remnants and improvements in dissection of the infrahyoid and posterior hyoid components, dissection between the hyoid and foramen cecum remains the final frontier. Garcia et al 28 studied serial pathology sections and found microscopic evidence of suprahyoid disease in 74% of primary TGDR resections and 100% of revision cases. Sistrunk had recognized that it was difficult to follow the thyroglossal duct tract above the hyoid.…”
Section: Discussionmentioning
confidence: 99%